Zakat Transformation in the Era of Society 5.0: Technology Optimization for Sustainable Social Welfare - Umami, Riza (West Science Islamic Studies, 2025)
The Society 5.0 era marks a paradigm shift in the use of technology to address social challenges sustainably. In this context, zakat as an Islamic social financial instrument has undergone a significant transformation. This study aims to analyze the role of technology in optimizing zakat management to improve the social welfare of the community. The research method used is a qualitative study with a descriptive-analytical approach through literature studies and secondary data. The results of the study indicate that digitalization of zakat through online platforms, integrated information systems, and the use of big data and artificial intelligence can improve distribution efficiency, transparency, and accountability. Technology also allows for the personalization of mustahik empowerment programs, so that social interventions can be more targeted. However, this transformation faces various challenges, including community digital literacy, infrastructure limitations, and data security issues. Therefore, collaboration between the government, zakat institutions, and the technology sector is essential to create an inclusive and sustainable digital zakat ecosystem. This study recommends an integrative strategy that combines technological approaches, policies, and sharia values ​​in zakat management to achieve holistic and equitable social development goals in the Society 5.0 era.